Etude de quelques métaux traces présents chez quelques espèces de caprélliens du golf d'Arzew - Bouharira, Sultana; Lekhal, Soumia Batoul (My University, 2022)
This work concerns a chemical study which consists in measuring the lead concentrated in the species Caprella danilevski at the level of two stations located on the coast of Mostaganem (Stidia and Salamander). To do this, several samples of C. danilevski were taken at the two stations (4 samples at Stidia and 3 at Salamander). Each Caprelle sample was dried and then mineralized in order to determine the lead level in this species by Atomic Absorption Spectrophotometry (SAA). The lead concentration averages in the Caprellians of the two Stidia stations and Salamander are 0.42 and 0.40 ppm respectively. A non-parametric “Kruskall-Wallis” test revealed that there is no significant geographical distance effect on the mean lead concentrations of the two stations. It would seem that the lead levels within the species C. danilevski between the two stations Stidia and Salamander are homogeneous. Furthermore, the lead level found in the populations of C. danilevski on the coast of Mostaganem is clearly higher than that found in later studies in the populations of the Strait of Gibraltar. Several factors such as the opportunistic diet of C. danilevski, discharges from the industrial zone of Arzew as well as urban and agricultural discharges could have an impact on lead concentrations at the Caprelles of Mostaganem. Finally, Caprella danilevski proved to be a potential indicator for future studies in the field of eco-toxicology.
Keywords: Caprelians; trace metals; SAA; Mostaganem